UV Fenton and sequencing batch reactor treatment of chlorpyrifos, cypermethrin and chlorothalonil pesticide wastewater - Affam, Augustine Chioma (Elsevier, 2014)
This study examined the effect of operating conditions of UV Fenton pretreatment combined with aerobic sequencing batch reactor on degradation and biodegradability (BOD5/COD ratio) improvement of chlorpyrifos, cypermethrin and chlorothalonil pesticide wastewater. The optimum operating conditions in the pretreatment phase were H2O2/COD molar ratio 2.0, H2O2/Fe2+ molar ratio 25, pH 3 and reaction time 60min and achieved COD and TOC removal were 64.8 and 45.9% for COD and TOC removal, respectively and biodegradabilty (BOD5/COD ratio) improved from 0.02 to 0.31. In the aerobic SBR phase, five different UV Fenton operating conditions were investigated and UV F-SBR 1 appeared to be the most significant (p<0.05). Increasing UV Fenton pretreatment time and combining the pretreated pesticide wastewater and municipal treatment plant wastewater enabled sustenance of the SBR operation. The UV Fenton-SBR (C) achieved COD and TOC removal efficiency of 96.2 and 97.4%, respectively after 40d operation at 12hr HRT. Effluent COD, TOC and BOD5 were 24, 19 and 18mgL-1, respectively and BOD5/COD ratio was 0.75. Applying the Monod model, values of the biological first order kinetic constant (Kob), cell yield (Yx/s) and decay coefficients (kd) were 0.1332hr-1, 0.5301 (mg COD mg-1 MLSS) and 0.0072hr-1, respectively. The UV Fenton-SBR (C) process is effective in treatment of pesticide wastewater containing chlorpyrifos, cypermethrin and chlorothalonil to meet Malaysian industrial effluent discharge standard.